Cashew residue biochar enhances the pore network of cohesive soil in the Brazilian Coastal Tablelands - Mota, Jaedson Cláudio Anunciato; dos Santos, Emanuela Barbosa; Queiroz, Alexandre dos Santos; Ferreira, Odair Pastor; de Souza Filho, Antônio Gomes; Fregolente, Laís Gomes; da Silva, Francisca Gleiciane; Pereira, Arthur Prudêncio de Araujo; Sousa, Helon Hébano de Freitas; Costa, Mirian Cristina Gomes; do Nascimento, Ícaro Vasconcelos (Geoderma Regional, 2025)
Soil physical quality is essential for agricultural productivity and environmental sustainability. Cohesive horizons often present high bulk density and low macroporosity, limiting water flow and aeration. This study evaluated the application of biochar derived from cashew residue as a conditioner to improve the physical quality of cohesive soils. We hypothesized that cashew residue biochar enhances soil (macro) porosity, pore connectivity, water retention, and water and airflow in cohesive horizons. The experiment was conducted with five biochar application rates (0, 5, 10, 20, and 40 Mg ha−1) in a randomized design, using disturbed soil samples manually packed into cylinders to ensure consistent bulk density. We analyzed the soil-water retention curve (SWRC), pore size distribution curve (PSDC), air permeability, pore continuity indices, and saturated hydraulic conductivity. Results demonstrated significant improvements in soil structure and pore functionality at higher biochar doses (20–40 Mg ha−1), despite the pore-blocking effect observed at these rates. The 40 Mg ha−1 treatment increased macroporosity by 15.3 %, while pore connectivity indices N and Log M rose by 34.2 % and 18.3 %, respectively. Available water improved by 9.1 %, and air permeability increased by 63.3 %, 45.0 %, 20.7 %, and 43.3 % at matric potentials of −6, −10, −33, and −100 kPa, respectively. Saturated hydraulic conductivity also increased by 18 % with the highest dose. These findings demonstrate the potential of cashew residue biochar to enhance the physical quality of cohesive soils, supporting more efficient soil management and sustainable agriculture. Applications between 20 and 40 Mg ha−1 are recommended to optimize improvements in soil physical properties.